About formation of stratum heterogeneity in the silicon single-crystals - Якименко, Анна Александровна; Червоный, Иван Федорович (Eastern-European Journal of Enterprise Technologies, 2014)
The analysis of the impurity accumulation in the melt at the crystallization front during the silicon single crystal growing was performed, and the model of rapid crystallization in this melt region was considered. The following impurity redistribution model was applied: during the crystallization of a single layer of silicon, one impurity part is absorbed by the growing crystal, while the other part remains in the melt, enriching its frontal area. During the crystallization of the second silicon layer, the growing crystal absorbs impurity from the impurity-enriched melt after crystallization of the first atomic layer, etc. Thus, in the frontal region of the melt, stepwise impurity accumulation and concentration supercooling region formation take place, including a possible increase in its concentration to the critical value - achieving the occurrence of independent second phase. According to calculations by the equation, growing rate increases by 5...7 times, and conditions for the abrupt change in the growing rate and crystallization of the impurity-enriched melt layer are ensured. After abrupt crystallization, the impurity accumulation to a certain value and accelerated crystallization mode are repeated in the frontal area. To eliminate or significantly reduce the strata characteristics, it is proposed to apply high-rate single crystal growing modes, which eliminates the impurity accumulation at the crystallization front and ensure its homogenous distribution by a single crystal volume.